The preferred IT sources and tools of Iranian people for accessing health information - Farzad Salmanizadeh; Nazanin Jannati; Leila Ahmadian; Yunes Jahani; Mohsen Balouchi; Reza Khajouei (BMC, 2023)
Abstract Introduction People need health information to maintain their health. Despite the variety of sources and tools for providing health information, there is little evidence about Iranian people's preferences in using these sources and tools. The objective of this study was to identify the preferred health information sources, tools, and methods for presenting health information in these tools. Methods This national survey was conducted among a sample of 4000 Iranian people between April and September 2021. The data was collected using a valid and reliable questionnaire (α = 0.86) consisting of four sections: participants' demographic information, current sources of obtaining health information, preferred information technology (IT) tools for accessing health information, and the method of presenting this information. Linear regression was used to investigate the relationship between demographic factors and other questions. Results The participants received health information mostly from the "Internet" (3.62), "family or friends" (3.43), "social networks" (3.41), "specific websites" (3.41), and "mobile apps" (3.27). "Social networks" (3.67), Internet "websites" (3.56), and "mobile apps" (3.50) were the most suitable tools for receiving health information. The participants preferred the presentation of health information in the form of "Images" (3.85), "educational videos" (3.69), and "texts" (3.53). Age, education, and marital status had a significant relationship with most of the preferred information sources, tools, and information presentation methods (p < 0.05). Conclusion The results of this study showed that Iranian people are more active information seekers than passive ones compared to a decade ago. The preferred sources and tools identified in this research can be used by healthcare planners and policy-makers in Iran and other developing countries to design and develop IT interventions that meet people's needs. Improving access to the Internet, social networks, and mobile apps and providing health information via images, educational videos, and texts on these platforms enhance access to the information people need.